Oral administration of resveratrol ameliorates epidermal hyperplasia in ultraviolet B irradiated BALB/c mice - Tava Shelan Nagapan, Ahmad Rohi Ghazali, Dayang Fredalina Basri, Wenna Nallance Lim (Journal of Applied Pharmaceutical Science, 2018)
Commercial sunscreens contain cosmetic preservatives which could exert phototoxic effect when exposed to sunlight. Natural sources, such as resveratrol, have gain attention in the cosmetic world as it has higher antioxidant capacity than vitamins C and E. Resveratrol also possesses strong anti-inflammatory, anti-cancer, and anti-aging properties. It also has proven to reduce epidermal hyperplasia and skin thickness. The aim of the study was to evaluate the ameliorative effect of resveratrol in reducing epidermal hyperplasia of mouse skin exposed to UVB irradiation. Eighteen female BALB/c mice were randomly divided into three groups: control group (n = 6), without Ultraviolet B irradiation and resveratrol administration; UVB exposure group (n = 6), irradiated with UVB dose of 250 mJ/cm2 for 3 minutes; and treatment group (n = 6), irradiated with UVB and treated with 0.02 ml of 200 mg/kg of resveratrol by oral gavage. Treatment was given for 14 days and UVB exposure was given on day 9, 11, and 13. On day 15, skin morphology was observed and skin-fold thickness was measured to evaluate edema. The mice were then sacrificed to obtain dorsal part of skin for histopathological observation using hematoxylin and eosin (H&E) stain. Resveratrol reduced skin scaling and erythema in UVB induced mice. Skin-fold thickness of resveratrol decreased significantly (p = 0.001) as compared to UVB irradiated group. H&E staining showed that resveratrol group reduced leukocyte infiltration and epidermal hyperplasia as compared to UVB exposure group. Hence, oral resveratrol was able to reduce skin thickness and epidermal hyperplasia and it has the potential to be developed as a natural alternative for photoprotection.
Keywords: Ultraviolet radiation, skin, resveratrol, BALB/c mice.